Body size, richness, and abundance of Staphylinidae unaffected by landscape composition and cropping system in a push–pull maize system in Kenya - Nina Garcia Devine; Tim Luttermoser; Katja Poveda (CABI Agriculture and Bioscience)
Abstract The change from predominantly natural to agricultural landscapes has been shown to reduce pollination and biological control services and also affect the functional traits of the insects that provide such services. Research shows that increasing agricultural area at the landscape scale can have variable effects on functional traits such as body size in predators. Moreover, local factors such as farm management strategies have also been shown to affect functional traits in insects. Studies of local or landscape effects on functional traits are often contradictory in temperate regions, and absent from tropical regions. In Kenya, local pest management technologies, e.g. push–pull systems have been shown to increase biological control, but data is lacking on how local management could affect body size of natural enemies. We investigated how the proportion of natural areas in the landscape and local management (push–pull) affected the body size of rove beetles (Staphylinidae) in Kenyan maize fields. Elytral and pronotal measurements were used to quantify body size, and a mixed-effects model was used to test the effect of landscape complexity and local management on the body size, richness, and abundance of rove beetles. We found no effect of landscape composition or local management on body size, richness, or abundance of rove beetles. We hypothesize that the lack of landscape effects could be caused by less plasticity in functional traits in tropical versus temperate zones. Our results demonstrate that changes in land use and local management do not always lead to changes in the diversity and functional traits of predator communities.